CONTINGENCY STUDY OF FINANCIAL FRAUD IN VILLAGES: THE ROLE OF LOVE OF MONEY, RELIGIOSITY, AND MORALITY - Liise, Sesika; Yamin, Nina Yusnita; Abdullah, M. Ikbal; Paranoan, Selmita; Yuniar, Latifah Sukmawati (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
Grounded in contingency theory, this study explores how religious beliefs and the love of money affect the propensity to commit fraud within the context of Village Financial Management, with morality examined as a moderating variable. Contingency theory posits that organizational behaviour and control effectiveness depend on situational factors; therefore, differences in moral standards, religious values, and financial attitudes may lead to varying tendencies toward fraudulent behaviour. The research was conducted in 64 village administrations in Sigi Regency, involving 117 village officials as respondents. SEM–PLS was used to analyze the data. The results show that love of money has a positive and significant effect on fraud tendency. In contrast, religiosity has no significant effect, indicating that religious values are not always reflected in financial behaviour. Morality also fails to moderate the impact of love of money on fraud. These findings highlight the dysfunction of authority and lack of functional separation that weaken anti-fraud efforts. The study emphasizes the need to strengthen internal control systems and cultivate ethics and integrity among village officials as part of improving accountability and supporting sustainable village development.